Renewing Digital Islamic Philanthropy for Education: Asset-Based Community Development - Shulhan Shulhan (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2026)
The purpose of this community service activity is to revitalize the digital platform of BAZNAS East Nusa Tenggara (NTT) to ensure robust management and verifiable accountability of accumulated educational philanthropic funds totaling IDR 264,962,420, while concurrently addressing an emergent institutional legitimacy crisis. The Asset-Based Community Development (ABCD) approach was employed over 4 weeks (16 sessions) and led by BAZNAS NTT through participatory training and mentorship. Data comprised qualitative measures (in-depth interviews and reflexive journaling) to assess the epistemic shift in organizational narrative, alongside quantitative indicators (financial disbursement verification and SOP adoption checklist) to evaluate performance metrics. The analysis was systematically structured using institutional and thematic frameworks (transformative learning) to map the underlying tension between mandated legitimacy and realized operational capacity. The principal findings are conclusive: the legitimacy crisis was successfully resolved, evidenced by the triumphant reactivation of the Kitabisa.com account and the verified disbursement of collected funds to intended beneficiaries. The intervention induced a critical epistemic shift and consolidated organizational capability (digital stewardship), underscoring the importance of activating endogenous moral capital to foster stakeholder ownership and long-term institutional sustainability. The outcome substantiates the occurrence of Transformative Learning. The community services validate a replicable ABCD model for zakat institutions operating in minority and peripheral regions. Theoretically, institutional sustainability is critically dependent on the organization's capacity to activate its endogenous moral capital as a prerequisite for structural and digital interventions.